1999
DOI: 10.1007/s003830050568
|View full text |Cite
|
Sign up to set email alerts
|

Accessory limbs associated with spina bifida - a second look

Abstract: An accessory limb associated with spina bifida was already reported by the authors. We had then described it as a result of a very early splitting of the limb bud arising from the paraxial mesoderm. We have subsequently seen three other such cases, which are described in this report as well as a review of five other cases in the literature. It is proposed that the growth of the accessory limb occurs from a mesodermal blastema that is a result of de-differentiation from Schwann cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 11 publications
1
29
0
1
Order By: Relevance
“…Krishna and Lal [6], in their series of 9 cases, supported the hypotheses of Gardner [7] and Egar [8]. Gardner [7] differentiated between primary and secondary neural-tube defects and suggested that while the former resulted from failure of the neural tube to close, the latter resulted from its rupture after closure due to oversecretion of neural tube fluid.…”
Section: Figsupporting
confidence: 63%
“…Krishna and Lal [6], in their series of 9 cases, supported the hypotheses of Gardner [7] and Egar [8]. Gardner [7] differentiated between primary and secondary neural-tube defects and suggested that while the former resulted from failure of the neural tube to close, the latter resulted from its rupture after closure due to oversecretion of neural tube fluid.…”
Section: Figsupporting
confidence: 63%
“…All were located at or near the dorsal midline. A review of the literature reveals another 7 cases [3,[6][7][8][9]. Of the 28 cases reported so far, including our patient, 17 were females and 5 were males, and in 5 cases, the sex was not reported.…”
Section: Discussionmentioning
confidence: 57%
“…The presence within the parasitic mass of polymorphic tissues, as well as organs and tissues belonging to several organ systems, would appear to support the theory of Spencer [4] that these lesions represent aborted or parasitic twinning . Significantly, Chadha et al [10] and Sharma et al [11] reported the presence of a benign teratoma within the parasitic mass, whereas a lipomatous mass was present within the parasite in other reported cases [6,9]. This indicates that, as has previously been suggested, there is a thin line of demarcation between teratomata, aborted duplications, fetal inclusions, more developed forms of parasitic twinning, and conjoined twins [10].…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations